Platformized Religiosity in Digital Games: A Critical Review of Roblox - Muhibudin Wijaya Laksana; Dody S. Truna; Roro Sri Rejeki Waluyajati (Jurnal Penelitian Agama, 2026)
This article explores how religiosity is expressed, negotiated, and commodified within digital spaces, focusing on the case of Roblox as a manifestation of the platform society. Using a critical-theoretical approach, it integrates Jürgen Habermas’s (1984) theory of communicative rationality, Nick Srnicek’s (2017) concept of platform capitalism, and a critique of Heidi A. Campbell’s (2012) notion of digital religion, further expanded through José van Dijck, Thomas Poell, and Martijn de Waal’s (2018) framework of the platform society. The analysis reveals that the expression, negotiation, and commodification of religiosity in digital environments represent a dialectical tension between communicative action and systemic rationality, where faith is mediated, structured, and governed by the technological and economic logic of platforms. Roblox functions as a microcosm of digital society, demonstrating how faith simultaneously thrives and is constrained under algorithmic control and data capitalism. The article contributes to religion and media studies by proposing the concept of platformized religiosity, a form of faith lived under algorithmic governance that nonetheless retains its reflective and emancipatory potential in modern digital life.